Atlantis II (Cruise 102) Moored and Shipboard Surface Meteorological Measurements During JASIN 1978. - Briscoe,Melbourne G; Mills,Carol A; Payne,Richard E; Peal,Kenneth R (1979)
During cruise 102 of the R/V Atlantis-II in the Joint Air-Sea Interaction Project (JASIN), surface meteorological data were gathered by Woods Hole Oceanographic Institution personnel from two moored buoys and from the ship. One buoy (JASIN W2/WHOI 651) carried a Vector Averaging Wind Recorder (VAWR) and a Vector Measuring Wind Recorder (VMWR); these instruments provided 18 days of intercomparison data and 38 days of meteorological data from 30 July to 6 September 1978. The other buoy (JASIN H2) carried a VMWR and gave 25 total days of data from 16 July to 10 August, and from 26 August to 1 September. A PET computer, hardwired to sensors positioned on the ship, displayed data that were logged during both legs of the cruise. Manual data were gathered by the science watches. This report describes the PET system, and displays and compares all the data. VAWR hourly meteorological data are listed for the 38 day period. Scientific interpretation of these data, such as calculations of heat fluxes, will be published separately. (Author) Sponsored in part by Grant NSF-OCE76-80174.